Classical Islamic Principles and the Current Model of Islamic Banking in Pakistan - Imran Hussain Minhas (Islamic Banking and Finance Review, 2021)
This paper is aimed to assess the overall perception of the users and stakeholders of Islamic banking towards Islamic banking and finance (IBF). It also intends to find out the crucial points which make the current practices of Islamic banking doubtful for the people and to suggest the appropriate remedial measures to bring about the practices of Islamic banking closer to the teachings of Islam and the Shari’ah. Direct survey method was used to assess and evaluate the perception of the users of Islamic banking and financé. However, the study was circumscribed by the opinions of the survey participants, who were limited in number and scattered across a few major cities of Pakistan. The findings revealed that a negative perception about Islamic banking persists due to the various similarities in the procedures, practices, products, and legal framework of Islamic and conventional banks. Moreover, the negative perception is also due to the fact that the same regulator regulates both the banking systems.KeywordsBanking laws and Regulations, Criticism, Islamic Banking and Finance, Perception, Regulator